ΜCT trait analysis reveals morphometric differences between domesticated temperate small grain cereals and their wild relatives. (10th April 2019) - Hughes, Aoife; Oliveira, Hugo R.; Fradgley, Nick; Corke, Fiona M. K.; Cockram, James; Doonan, John H.; Nibau, Candida
Summary: Wheat and barley are two of the founder crops domesticated in the Fertile Crescent, and currently represent crops of major economic importance in temperate regions. Due to impacts on yield, quality and end‐use, grain morphometric traits remain an important goal for modern breeding programmes and are believed to have been selected for by human populations. To directly and accurately assess the three‐dimensional (3D) characteristics of grains, we combine X‐ray microcomputed tomography (μCT) imaging techniques with bespoke image analysis tools and mathematical modelling to investigate how grain size and shape vary across wild and domesticated wheat and barley. We find that grain depth and, to a lesser extent, width are major drivers of shape change and that these traits are still relatively plastic in modern bread wheat varieties. Significant changes in grain depth are also observed to be associated with differences in ploidy. Finally, we present a model that can accurately predict the wild or domesticated status of a grain from a given taxa based on the relationship between three morphometric parameters (length, width and depth) and suggest its general applicability to both archaeological identification studies and breeding programmes. Significance Statement: Small grain cereals provide the bulk of human calorific intake both directly and indirectly through their use for livestock feed. We present tools based on μCT scanning to morphometrically model differences in grain shape in wild and domesticated wheat and barley. This approach provides insights into past and ongoing changes in grain shape in small grain cereals.